Happiness Level and Happiness Portrayal among Tertiary Education Institutions Educators - Jr, Pedro P. Raymunde; Caballo, John Harry S. (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study was conducted to determine the level of the happiness of educators, the level of happiness portrayal of educators, and the significant relationship between the happiness and happiness portrayal of educators. This study employed a quantitative correlational research design. Furthermore, this study administered two types of standardized tests to gather the data needed. The results implied that the educators’ level of happiness is high. On the other hand, the level of happiness portrayal of educators is also high. In addition, the reflected standard deviation for each of the variables, namely the happiness and happiness portrayal, was found to be quite varied. Further analysis revealed that there is a positive moderate significant relationship between the educators’ happiness and happiness portrayal (r= .55, p> .05). Consequently, the institutions should be able to provide an avenue to increase the happiness of the educators in terms of their professional and personal lives.